Active noise control of a diesel generator in a luxury yacht. (April 2016) - Cheer, Jordan; Elliott, Stephen J.
Abstract: Active noise control has been applied to a variety of systems in order to improve performance without the increases in size and weight that would otherwise be required by traditional passive noise control treatments. This paper investigates the application of an active noise control system to the control of generator noise in the master cabin of a luxury yacht. A multichannel, multi-tonal active noise control system employing loudspeakers and microphones in the master cabin of the yacht is investigated. It is shown that, due to the high number of engine orders produced by the generator, in order to achieve significantly perceptible levels of noise attenuation it is necessary to control at least 7 individual orders. A controller is investigated which targets 19 engine orders and it is shown to achieve in excess of 5 dB broadband attenuation, whilst achieving up to 23 dB attenuation in individual orders. This corresponds to a 23% reduction in the Zwicker loudness.